Eating Habits and Dietary Strategies of the Glass Perchlet Fish (Ambassis macracanthus) In Benoa Bay Waters, Bali in Two Different Seasons - Julian Ichsana Argeswara; Nyoman Dati Pertami; Gde Raka Angga Kartika (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2024)
The Benoa Bay area and its surroundings are a center of biodiversity at the ecosystem level in the southern coastal region of Bali. This area exhibits diverse ecosystems, including mangrove ecosystems, coral reefs, seagrass beds, and tidal flats. This research aims to analyze and describe the feeding ecology of Ambassis macracanthus in the waters of Benoa Bay. The study was conducted in May, at the end of the transitional season, and in July and August, during the eastern monsoon season in Benoa Bay Waters. Modified gill nets with mesh sizes of 0.5, 1.0, 1.5, 2.0, 2.5, and 3.0 cm were used for capturing the fish. The fish were caught at three stations, which represented the characteristic conditions of the Benoa Bay Waters. Out of the 396 individuals caught during the study, only 100 were selected for examination. The average relative fullness gut index (RGI) of Ambassis macracanthus ranged from 0.39 to 0.67. The total Important Relative Index (IRI) value for the food of Ambassis macracanthus in Benoa Bay Waters was 951.27. Ambassis macracanthus in Benoa Bay Waters is an omnivorous species with a tendency towards herbivory, and 21 different organisms were found in its diet, including three classes of phytoplankton and three classes of zooplankton. The feeding strategy developed by Ambassis macracanthus in Benoa Bay Waters is generalist. This information about the fish can be used as a fundamental basis for managing fish in the waters of Benoa Bay.